Introduction to universal design - Clokey, Jora; Harrigan, Jim; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2004)
Presents a brief history of how the philosophy of accessibility, known as universal design, has emerged. This program shows how designers meet requirements of the Americans With Disabilities Act (ADA), including discussion of how attitudinal and physical barriers to accessibility arise and how to minimize them. This video defines the concept of a continuous path of travel and presents design criteria
Title from title screen
Camera, Joe Clokey, Jim Harrigan ; music, Russell Autrey
DVD format
Keywords: Barrier-free design; Architecture -- Designs and plans; Landscape design